The Relationship Between Financing Management Policy And Madrasah Quality Improvement - Wahyu Hidayat; Nifasri; Riani Ratna Puri (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2024)
Improving the quality of education is a development target in the national education sector and is an integral part of efforts to improve the quality of Indonesian people as a whole. One of the government's solutions to improving the quality of education is to create a financing management policy. This research aims to describe the relationship between financing management policies and quality improvement in Madrasas at MTsN 1 and MTsN 3 Garut. The approach used in this research is quantitative, descriptive method of correlational analysis. Data collection in this research was obtained through a questionnaire with Likert scale data measurements. The respondents of this research were 33 teaching and education staff at MTsN 1 and MTsN 3 Garut. Based on the research results, it shows the relationship between financing management policies and improving the quality of madrasas based on a correlation test, there is a significant correlation between the financing management policy variable (X) and the variable improving the quality of madrasas (Y), this is due to the significance value of Sig. (2- tailed) 0.01 < 0.05. Based on rcount (Peiarson correlation) it is known that the relationship between the two variables is 0.432 > rtabeil 0.344, Peiarson correlation has a positive value, so the correlation between variables is positive with the criteria for a relationship that is large enough or strong enough. Furthermore, the results of the coefficient of determination are equal to 0.386, which means that the contribution of financing management policy (X) to the variable of increasing the quality of madrasas (Y) is equal to 38.6%. Thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.